Comparison of insertion torque, implant stability quotient and removal torque, in two different implant designs with and without osseodensification. - An ex vivo bench top study - Yazad Gandhi; Ninad Padhye (Elsevier, 2023)
Background: Primary stability is an important factor in influencing the outcome of dental implants. Osteotomy modification techniques mentioned, include osteotomes for bone condensation, under-preparation of osteotomy and Osseodensification (OD). The objective of our twin arm study was to assess how two different implant designs respond to conventional osteotomy drilling and how these values obtained compare with OD. Materials and methods: The study comprised a total of 80 implants inserted in pig tibia bone. Group 1a (n = 20) consisted of tapered internal implants and group 1b (n = 20) consisted of tapered pro implants, both inserted with conventional drilling. Group 2a (n = 20) consisted of tapered internal implants and group 2b (n = 20) consisted of tapered pro implants, both inserted with OD. Each implant inserted was measured for implant stability quotient (ISQ), insertion torque and removal torque. Results: Group 1a showed a significantly lower ISQ, mean insertion and removal torque and as compared to Group 1b. Group 2a and 2b had comparable mean values for all the three parameters. Inter-group comparison showed a higher ISQ and insertion torque value for group 2 than group 1. Intra-group assessment showed a significantly lower value for all parameters for sub-group a than b. Conclusions: OD enhances primary stability of implants in bone; but when no OD is used, the tapered pro implant design offers a better primary stability. This may be attributed to the active thread design.